Risk assessment tools in criminal justice and forensic psychiatry: the need for better data - Fazel, S; Douglas, T; Singh, I; Savulescu, J; Pugh, J (Elsevier, 2016)
Violence risk assessment tools are increasingly used within criminal justice and forensic psychiatry, however there is little relevant, reliable and unbiased data regarding their predictive accuracy. We argue that such data are needed to (i) prevent excessive reliance on risk assessment scores, (ii) allow matching of different risk assessment tools to different contexts of application, (iii) protect against problematic forms of discrimination and stigmatisation, and (iv) ensure that contentious demographic variables are not prematurely removed from risk assessment tools.